The Magic Toyshop: A narrativa imagética como processo de recriação - Rodrigues, Talita Annunciato [UNESP]; Rapucci, Cleide Antonia [UNESP] (Universidade Estadual de Maringa, 2013)
Because it belongs to a cultural practice, the adaptation of a novel into a feature film will always exist within a context and, for being subject to changes, corresponding modifications in the political sphere and even variations in the meaning of the story may occur. This seems to be precisely the result of the transformation of Angela Carter's second novel, The Magic Toyshop, into the homonymous film, directed by David Whealtey in 1987. Removed from the context of the book's production and publication, a crucial period of questioning about the importance of women in society and culture, the plot created by the English author in the sixties, rewritten two decades later, with the author herself as the script writer, seems to have acquired another meaning during this time. Although the film maintains the same plot of the novel, the political engagement visibly present in the narrative, namely Carter's critical stance about the model of patriarchal society, seems to lose its strength, highlighting now its fantastic character. Briefly discussing issues such as loyalty and betrayal of one gender to another, we seek in this paper to observe the film, based on the re-writers perspective, in other words, the prospects of both writer and director, as a process of rebuilding the story. In this dialogue, the script was also used as an intertext for a better understanding of this process.
The Magic Toyshop: The filmic narrative as a recreation process
Keywords: Angela Carter; Cinema; English literature; Recreation